Efektivitas Hukum Penyelenggaraan Sistem Jaminan Sosial Nasional ( Studi Terhadap Kinerja Badan Penyelenggara Jaminan Sosial Program Kesehatan di Kota Solo ) - Tarsanto, Tarsanto (2016)
In The Act No 24 of 2011 about National Social Security System submitted to BPJS is tremendous step forward for prosperity to the Indonesian peoples, although there is still chaos in its implementation. It is necessary to know, how implementation and how ideal policies foresable future. Legal practicioners made useful in put to improving the regulations and also for the public to know their rights obligatiosn are quaranteed by the state health services. By using qualitative research and technical analysis of triangulation, will be described the legal aspects that need to be refined in order to pressure the effectiveness of the implementation of a more fitting that on the social rights of health,legal position BPJS, criminal provisions, dispute and settlement in the Act. And as a conclusion can be drawn that BPJS Kesehatan them should not involve discrimination, public legal body which should not be doing business, should regulate criminal provisions in the event of a dispute and settlement between the parties concerned.